The Benefits of Aerobic Dance on Physical Fitness: A Literature Review - Poppy Elisano Arfanda; Andi Muh Ridwan Anwar; Shobirotus Soraya; F Devi Kurnia; Fini May Putriani (Jurnal Ilmu Keolahragaan, 2025)
Aerobic dance is a form of rhythmic aerobic exercise that combines movement with music, thereby enhancing physical fitness as well as exercise motivation. This literature review aims to analyze the effectiveness of aerobic dance in improving physical fitness based on the latest scientific evidence. Articles were searched through Scopus, PubMed, and Google Scholar databases using the keywords “aerobic dance,” “VO₂max,” “physical fitness,” and “body composition,” covering publications from 2022–2025. Based on inclusion and exclusion criteria, 6 articles were selected and analyzed in depth using the annotated bibliography method. The findings indicate that aerobic dance consistently improves cardiorespiratory capacity, VO₂max, and body composition, while also providing psychological benefits such as reduced stress, improved mood, and better quality of life. Interventions lasting 8–12 weeks with moderate-to-high intensity were found to be the most effective in producing significant physiological adaptations. Moreover, population characteristics such as age, baseline fitness level, and training adherence influence the outcomes. This review emphasizes that aerobic dance is a flexible, low-cost, and evidence-based exercise strategy for enhancing physical fitness. However, further large-scale experimental studies are needed to strengthen the generalizability of these findings.